Perancangan Sistem Informasi Imunisasi Dasar Lengkap (IDL) Menggunakan Teknologi SMS Gateway - Evasaria Magdalena Sipayung; Herastia Maharani; Tamsir H. Sirait; Erik Gunawan (Ikatan Ahli Informatika Indonesia, 2018)
Immunization is one effort to improve the health (promotion) and disease prevention (preventive) thoroughly and continuously. Immunization has become mandatory in Indonesia, especially for children under the age of 12 years. Currently there are health centers that do not have a historical immunization record of each baby so the records of immunizing all babies are merged into one book. Currently the processing of delivers information held by health care facilities is still using the immunization schedule card provided during registration immunization program. Accordingly communication between health care facilities with parents of babies is not efficient. Therefore the aim of this research is to produce the design of immunization information system that helps the health care facilities to provide information and data about immunization schedule each of baby. On systems that have been designed, the health center can obtain data and information of the babies that follows immunization program quickly, providing an accurate historical data record of immunization and information about immunization schedule would do next. By using SMS Gateway technology that could remind and warned parents about schedules and types of immunization to be received next through these technologies.